Curriculum Innovation through Master of Ceremony Workshops among Female Students at Modern Islamic Boarding Schools - Fairuz Subakir Ahmad; Agus Yasin; Ahmad Ario Sofian; Nur Fera Khalifah; Nuraeni Rahmawati (Universitas Nurul Jadid, 2025)
This study examines the implementation of Arabic Master of Ceremony (MC) workshops as a form of curriculum innovation in enhancing communicative competence among female students at Pondok Modern Darussalam Gontor Putri Campus 1. The research employed a qualitative case study approach involving language coordinators, workshop instructors, teachers, and female students selected purposively based on their participation in the program. Data were collected through observation, in-depth interviews, and documentation, and analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings reveal that Arabic MC workshops function not only as extracurricular activities but also as performance-based learning strategies integrated into the pesantren curriculum and institutional culture. The workshops contributed significantly to improving students’ Arabic speaking fluency, public speaking confidence, leadership skills, and organizational participation through authentic communicative practices. Furthermore, the program operated as a hidden curriculum transmitting discipline, responsibility, communication ethics, and institutional values through mentoring and collective participation. The study concludes that Arabic MC workshops represent an innovative educational model integrating communicative language teaching, experiential learning, and character formation within Islamic boarding school education. This study contributes theoretically to curriculum innovation discourse and practically offers an alternative model for performance-based Arabic language learning in pesantren contexts.